Strategy of Competitiveness Improvement of West Java Industry - Ina Primiana (Universitas Trisakti, 2007)
The issue of competitiveness in local, national or international markets is a key issue and tough challenge for industry in West Java. Without sufficient ability and high competitive advantage,it is impossible for the products of West Java industry to penetrate the market. Furhermore, imported products can put domestic market in danger. Therefore, some efforts to improve competitiveness and create competitive advantage of the products of West Java industry can no longer be postponed. Moreover, it should be the focus of attention of not only business society, but also bureaucracy officials, various organizations and community, which is an industry working environtment. Study purpose (a) Obtaining clear picture of the problem from internal and external points of view which inhibits competitiveness improvement of West Java industry, (b) creating planning of competitiveness improvement of West Java industry as the basis of provincial government policy in advancing local industry. The result of study shows that there are 4 main determinants and I supporting determinant which have to be the focus of attention of industry competitiveness improvement.